Allied Decoupling in an Era of US–China Strategic Competition. (21st December 2020) - Cha, Victor D
Abstract: The turn towards an openly competitive relationship between the United States and China today carries acute consequences for U.S. policy toward North Korea (Democratic People's Republic of Korea or DPRK) and South Korea (Republic of Korea or ROK). The military and economic requirements of enacting such a policy of competition with China complicates U.S. policy with its ally South Korea, as it exacerbates three core dilemmas that the ROK contends with regarding China. These dilemmas compel choices for a U.S. ally that must increasingly become zero-sum in nature where Seoul must make choices that alienate its patron ally or its neighbor. This article draws out propositions for how changes in U.S.-China relations impacts strategy on both sides of the Korean peninsula. The primary finding is that changes in the independent variable (U.S.-China relations) have opposing impacts on South Korean and North Korean strategic thinking (dependent variable). What might be considered opportunities afforded by U.S.-China relations to South Korea are seen as threats by North Korea. Conversely opportunities created by U.S.-China relations for North Korea register as threats for South Korea.